Clinicopathological Significance of FOXO4 Expression and Correlation with Prx1 in Head and Neck Squamous Cell Carcinoma. (18th May 2021) - Lu, Yunping; Shen, Yajun; Li, Lingyu; Zhang, Min; Wang, Min; Ge, Lihua; Yang, Jing; Tang, Xiaofei
Abstract : Objective . Forkhead box O 4 (FOXO4), a key albumen in the forkhead box O (FOXOs) family, plays crucial roles as a tumor suppressor in the cancer development. In our previous study, Peroxiredoxin1 (Prx1) promoted the development of oral cancer and was predicted to bind to FOXO4. The aim of this study was to investigate the clinicopathological significance of FOXO4 expression and its potential mechanism in head and neck squamous cell carcinomas (HNSCC). Methods . The function of FOXO4 correlation with HNSCC prognosis was analyzed via ONCOMINE, UALCAN, Human Protein Atlas, and cBioPortal. The expression of FOXO4 was detected in Prx1 silenced CaL27 and SCC9 cell lines by Western blot. FOXO4 protein expression was observed via immunohistochemistry (IHC) and the binding of Prx1 to FOXO4 measured by Duolink analysis in a 4-nitro-quinoline-1-oxide- (4NQO-) induced tongue carcinogenesis model in Prx1 +/+ and Prx1 +/− mice. Results . By the analysis of Bioinformation Databases, there was a significant interaction of FOXO4 down expression to clinical tumor stages and pathological grades in the patients with HNSCC. Reduced mRNA and protein expression of FOXO4 were found to be significantly correlated with the poor overall survival (OS) of HNSCC patients. FOXO4 expression is negatively related to Prx1 significantly in HNSCC tissues. By employing a 4NQO-induced oral carcinogenesis mouse model, we confirmed that FOXO4 expression was reduced in 4NQO-induced squamous cell carcinoma (SCC) tongue tissues compared with those in normal tissues. Prx1 knockdown resulted in the upregulation of FOXO4 expression in the SCC tissues and CaL27 and SCC9 cell lines. Furthermore, the interaction of Prx1 with FOXO4 was observed in mouse tongue tissues by Duolink analysis. Conclusion . FOXO4 plays an important role in the development of HNSCC. The lower expression of FOXO4 is significantly correlated with the shorter OS in patients with HNSCC. FOXO4 is negatively regulated via interaction with Prx1. FOXO4 could be a potential molecular target for the treatment and prognosis of HNSCC.